2017
DOI: 10.1371/journal.pone.0175346
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between temperaments, occupational stress, and insomnia among Japanese workers

Abstract: Insomnia among workers reduces the quality of life, contributes toward the economic burden of healthcare costs and losses in work performance. The relationship between occupational stress and insomnia has been reported in previous studies, but there has been little attention to temperament in occupational safety and health research. The aim of this study was to clarify the relationships between temperament, occupational stress, and insomnia. The subjects were 133 Japanese daytime local government employees. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 55 publications
2
18
0
1
Order By: Relevance
“…Fifth, our results may have been influenced by residual confounding from unmeasured variables, such as stress coping style, personality, and temperament [ 44 , 45 ]. Future study needs to consider individual factors, such as personality or temperament, as we previously reported [ 46 ]. Sixth, the representativeness of this study sample is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, our results may have been influenced by residual confounding from unmeasured variables, such as stress coping style, personality, and temperament [ 44 , 45 ]. Future study needs to consider individual factors, such as personality or temperament, as we previously reported [ 46 ]. Sixth, the representativeness of this study sample is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous epidemiological studies examining the association between work-related stress and sleep quality have demonstrated that work-related stress is a major factor in disturbing sleep quality [ 16 ]. Current evidence suggests that workers exposed to chronic psychological job stressors develop sleep problems as a reaction to this stress [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of work-related stress on the physical and mental health of populations from different occupations recently become of great interest. Some studies have demonstrated the relationship between insomnia and various types on occupational stress, such as job demand, job control, social support, job insecurity, organizational justice, intragroup conflict, job strain, effort–reward imbalance, employment level, and shift work [ 16 ]. A group of Japanese scholars have published on the relationship between job stress and sleep quality, and the results suggest that job stress is indeed associated with sleep quality, and that it increases the risk of experiencing sleep problems [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research concluded that work-related stress is associated and increase an individual's vulnerability to burnout, job satisfaction and physical as well as mental health outcomes (Piko, 2006;Pillay, 2009). Other health problems related to the effects of work stress include: cardiovascular disorders (Li, Loerbroks, Bosma, & Angerer, 2016), gastrointestinal disorders (Huerta-Franco, 2013), musculoskeletal disorders (Nafeesa, Vidhya, Vijayalakshmi, & Rajkumar, 2017), anxiety and depression (Fan, Blumenthal, Watkins, & Sherwood, 2015), work fatigue (Rose et al, 2017), insomnia (Deguchi et al, 2017), alcohol abuse (Moore, Sikora, Grunberg, & Greenberg, 2007), decrease marital quality (Obradović & Čudina-Obradović, 2013) and disruption of social interaction (La Torre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%